Synthesis, characterization, and ammonia sensing performance of poly(3-hydroxybutyrate) grafted multiwall carbon nanotubes. Issue 1 (2nd January 2022) - Qazi, Raina Aman; Ali Shah, Luqman; Ullah, Rizwan; Khattak, Rozina; Sadiq, Muhammad; Saleem Khan, Mohammad
ABSTRACT: Poly(3-hydroxybutyrate) grafted multiwall carbon nanotubes (g-MWCNTs) were synthesized while using purified MWCNTs ( p -MWCNTs). Functionalization of MWCNTs was confirmed by FTIR, TGA, and XRD measurement. Comparative study of ammonia sensing performance of p -MWCNTs, carboxylated MWCNTs (a-MWCNTs), amine-functionalized MWCNTs (f-MWCNTs) and g-MWCNTs were performed. Among all g-MWCNTs showed a large variation in resistance over an entire concentration range of ammonia vapors. The calculated limit of detection for g-MWCNTs was found to be 0.236 ppm. Sensor response of g-MWCNTs reaches full saturation at 150 ppm ammonia. The f-MWCNTs and g-MWCNTs showed a highly reversible response to ammonia vapors at 250 ppm at 25°C.